Dialogue with the public: A catalyst for professional identity formation in medical students - Masashi Ikuno; Akiko Tokinobu; Tomoko Miyoshi; Hitomi Kataoka (PLoS ONE, 2025)
Objectives This study aimed to explore how Japanese medical students are influenced by their dialogue with the general public as part of the process of professional identity formation. These findings are expected to provide insights into supporting the development of professional identity from diverse perspectives, particularly for medical students in the pre-stage of legitimate peripheral participation and those currently engaged in it. Methods Semi-structured interviews were conducted with three medical students of different backgrounds. These students participated in a dialogue-based event with the general public, in which they ran a booth focused on medical education. A qualitative descriptive approach was adopted and an interpretivist study was conducted through a thematic analysis. Data were analyzed using the Steps for Coding and Theorization (SCAT) qualitative data analysis method. Results The students reflected on their dialogue with the general public about medical education and discussed infrequent opportunities to recognize or disclose their professional identity in daily life. A preclinical student (third-year) noted, “I felt like I shared a similar sense of amazement with the visitors” and “It’s obvious, but I really came to realize that I’m seen from the perspective of a medical student or a healthcare professional.” In contrast, a clinical student (fifth-year) reflected, “Sharing my feelings about whether I’ve been helping others during my clinical training felt closely tied to me—there wasn’t much of a gap.” SCAT analysis revealed that preclinical students emphasized ‘reaffirming their professional identity through empathetic understanding,’ while clinical students focused on ‘disclosing their professional identity, leading to its integration with their personal identity.’. Conclusion Dialogue with the general public unexpectedly enhanced medical students’ awareness of their professional identity. In the process of professional identity formation, dialogue with the general public can support the traditionally emphasized socialization process through participation in professional groups, particularly by facilitating the reaffirming of professional identity and its integration with personal identity.